Position of dietitians of Canada, the American Dietetic Association, and the American College of Sports Medicine: Nutrition and athletic Performance (2000)
It is the position of Dietitians of Canada, the American Dietetic Association, and the American College of Sports Medicine that physical activity, athletic performance, and recovery from exercise are enhanced by optimal nutrition. These organizations recommend appropriate selection of food and fluids, timing of intake, and supplement choices for optimal health and exercise performance. This position paper reviews the current scientific data related to athletes` energy needs, assessment of body composition, strategies for weight change, athletes` nutrient and fluid needs, special nutrient needs during training, the use of supplements and nutritional ergogenic aids, and nutrition recommendations for vegetarian athletes. During times of high physical activity, energy and macronutrient needs—especially carbohydrate and protein intake—must be met in order to maintain body weight, replenish glycogen stores, and provide adequate protein for building and repairing tissue. Fat intake should be adequate to provide essential fatty acids and fat-soluble vitamins, as well as to help provide adequate energy for weight maintenance. Overall, diets should provide moderate amounts of energy from fat (20- 25% of energy); there appears to be no health or performance benefit to consuming a diet containing less than 15% of energy from fat. Body weight and composition can affect exercise performance, but should not be used as the sole criterion for sports performance; daily weigh-ins are discouraged. Consuming adequate food and fluid before, during, and after exercise can help maintain blood glucose levels during exercise, maximize exercise performance, and improve recovery time. Athletes should be well hydrated before beginning exercise; they should also drink enough fluid during and after exercise to balance fluid losses. Consumption of sport drinks containing carbohydrates and electrolytes during exercise will provide fuel for the muscles, help maintain blood glucose levels and the thirst mechanism, and decrease the risk of dehydration or hyponatremia. Athletes will not need vitamin-and-mineral supplements if adequate energy to maintain body weight is consumed from a variety of foods. However, supplements may be required by athletes who restrict energy intake, have severe weight-loss practices, eliminate one or more food groups from their diet, or consume high-carbohydrate diets with low micronutrient density. Nutritional ergogenic aids should be used with caution, and only after careful evaluation of the product for safety, for efficacy, for potency, and to determine whether or not it is a banned or illegal substance. Nutrition advice, by a qualified nutrition expert, should be provided only after the athlete`s health, diet, supplement and drug use, and energy requirements have been carefully reviewed.